Observations of the low-luminosity Type Iax supernova 2019gsc: a fainter clone of SN 2008ha? - Lina Tomasella; Maximilian Stritzinger; Stefano Benetti; Nancy Elias-Rosa; Enrico Cappellaro; Erkki Kankare; Peter Lundqvist; Mark Magee; Kate Maguire; Andrea Pastorello; Simon Prentice; Andrea Reguitti (OXFORD UNIV PRESS, 2022)
We present optical photometric and spectroscopic observations of the faint-and-fast evolving Type Iax supernova (SN) 2019gsc, extending from the time of g-band maximum until about 50 d post-maximum, when the object faded to an apparent r-band magnitude m(r )= 22.48 +/- 0.11 mag. SN 2019gsc reached a peak luminosity of only M-g = -13.58 +/- 0.15 mag, and is characterized with a post-maximum decline rate Delta m(15)(g) = 1.08 +/- 0.14 mag. These light curve parameters are comparable to those measured for SN 2008ha of M-g = -13.89 +/- 0.14 mag at peak and Delta m(15)(g) =1.80 +/- 0.03 mag. The spectral features of SN 2019gsc also resemble those of SN 2008ha at similar phases. This includes both the extremely low ejecta velocity at maximum, similar to 3000 km s(-1) and at late-time (phase +54 d) strong forbidden iron and cobalt lines as well as both forbidden and permitted calcium features. Furthermore, akin to SN 2008ha, the bolometric light curve of SN 2019gsc is consistent with the production of approximate to 0.003 +/- 0.001 M-circle dot of Ni-56. The explosion parameters, M-ej approximate to 0.13 M-circle dot and E-k approximate to 12 x 10(48) erg, are also similar to those inferred for SN 2008ha. We estimate a subsolar oxygen abundance for the host galaxy of SN 2019gsc (12 + log(10)(O/H) =8.10 +/- 0.18 dex), consistent with the equally metal-poor environment of SN 2008ha. Altogether, our data set for SN 2019gsc indicates that this is a member of a small but growing group of extreme SN Iax that includes SN 2008ha and SN 2010ae.